The Impact of Greenwashing on Perceived Environmental Performance Toward Brand Avoidance and Brand Switching - Ibau, Silviana; Kholid Mawardi, Mukhammad; Rahimah, Anni (Profit: Jurnal Adminsitrasi Bisnis, 2025)
This study uses a case study of Le Minerale gallon users to examine how greenwashing affects perceived environmental performance, brand avoidance, and brand switching. "Greenwashing" is the practice of misleading consumers by claiming, for a commodity or service, environmental friendliness while it is not. This study uses explanatory quantitative research to examine causal relationships between variables among Le Minerale customers in Malang Raya, with 210 data collected through structured instruments. This study focuses on brand avoidance and switching, especially how perceived environmental performance (PEP) affects them. The study found that greenwashing negatively impacts consumers' PEP, significantly increasing both brand avoidance and brand switching, as consumers become skeptical of misleading environmental claims and prefer more trustworthy, eco-friendly alternatives. The practical implication of this research is its potential to guide marketers and business practitioners in adopting more transparent and authentic green marketing strategies to build consumer trust and loyalty.